2014
DOI: 10.1088/0004-637x/786/1/57
|View full text |Cite
|
Sign up to set email alerts
|

THE LUMINOSITY FUNCTION ATz∼ 8 FROM 97Y-BAND DROPOUTS: INFERENCES ABOUT REIONIZATION

Abstract: We present the largest search to date for Y-band dropout galaxies (z ∼ 8 Lyman break galaxies, LBGs) based on 350 arcmin 2 of HST observations in the V-, Y-, J-and H-bands from the Brightest of Reionizing Galaxies (BoRG) survey. In addition to previously published data, the BoRG13 dataset presented here includes approximately 50 arcmin 2 of new data and deeper observations of two previous BoRG pointings, from which we present 9 new z ∼ 8 LBG candidates, bringing the total number of BoRG Y-band dropouts to 38 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
247
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 146 publications
(270 citation statements)
references
References 80 publications
22
247
1
Order By: Relevance
“…The best-fit parameters are in good agreement with observations (Schmidt et al 2014;Bowler et al 2015;Oesch et al 2010;Finkelstein et al 2015b;Bouwens et al 2015b) given the large degeneracies in Schechter function parameters. Encouragingly, we find the evolution of the derived Schechter parameters is in excellent agreement with the observed evolution (Bouwens et al 2015b;Bowler et al 2015): we find dα/dz ∼ −0.1, dM * /dz ∼ 0.1, and d log(Φ * )/dz ∼ −0.3 between z ∼ 4 and z ∼ 8.…”
Section: Luminosity Functions and Sfr Densitysupporting
confidence: 79%
See 3 more Smart Citations
“…The best-fit parameters are in good agreement with observations (Schmidt et al 2014;Bowler et al 2015;Oesch et al 2010;Finkelstein et al 2015b;Bouwens et al 2015b) given the large degeneracies in Schechter function parameters. Encouragingly, we find the evolution of the derived Schechter parameters is in excellent agreement with the observed evolution (Bouwens et al 2015b;Bowler et al 2015): we find dα/dz ∼ −0.1, dM * /dz ∼ 0.1, and d log(Φ * )/dz ∼ −0.3 between z ∼ 4 and z ∼ 8.…”
Section: Luminosity Functions and Sfr Densitysupporting
confidence: 79%
“…The picture emerging from these observations is that the number density of galaxies decreases with increasing redshift, while the LF remains consistent with a Schechter (1976) form, Φ(L) = Φ * (L/L * ) α exp (−L/L * )/L * out to z ∼ 8, albeit the uncertainty and co-variance in the best fitting parameters grows at high redshift (Schmidt et al 2014;Bouwens et al 2015b). However, other studies find either an equally good fit with a double-power law at z ∼ 8 (Finkelstein et al 2015b), or a preference for the double power law at z ∼ 7 (Bowler et al 2014;Bowler et al 2015; but note that the z ∼ 7 investigations are based on ground, rather than space observations).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…As of 2016 there are now ∼1000 candidate objects, encompassing a wide range of luminosities, identified (e.g. Bouwens et al 2010Bouwens et al , 2011Bouwens et al , 2014aBouwens et al ,b, 2015aOesch et al 2010Oesch et al , 2013Oesch et al , 2014Oesch et al , 2015Oesch et al , 2016Bunker et al 2010;Wilkins et al 2010Wilkins et al , 2011aFinkelstein et al 2010Finkelstein et al , 2012Finkelstein et al , 2015Lorenzoni et al 2011Lorenzoni et al , 2013McLure et al 2011McLure et al , 2013Ellis et al 2013;Laporte et al 2014Laporte et al , 2015Laporte et al , 2016Schmidt et al 2014;McLeod et al 2015;McLeod, McLure & Dunlop 2016;Atek et al 2015a, Atek et al2015b) with the first small samples now identified at z ∼ 10 and beyond.…”
Section: Introductionmentioning
confidence: 99%